Staging of T1 esophageal adenocarcinoma with volumetric laser endomicroscopy: a feasibility study - Allon Kahn; Amrit K. Kamboj; Prasuna Muppa; Tarek Sawas; Lori S. Lutzke; Matthew R. Buras; Michael A. Golafshar; David A. Katzka; Prasad G. Iyer; Thomas C. Smyrk; Kenneth K. Wang; Cadman L. Leggett (Endoscopy International Open, 2019)
Background and study aims Precise staging in T1 esophageal adenocarcinoma (EAC) is critical in determining candidacy for curative endoscopic resection. High-frequency endoscopic ultrasound (EUS) has demonstrated suboptimal accuracy in T1 EAC staging due to insufficient spatial resolution. Volumetric laser endomicroscopy (VLE) allows for high-resolution wide-field visualization of the esophageal microstructure. We aimed to investigate the role of VLE in staging T1 EAC. Patients and methods Patients undergoing endoscopic mucosal resection (EMR) were prospectively enrolled and only T1 EAC cases were included. EMR specimens were imaged using second-generation VLE immediately after resection. VLE images were analyzed for signal intensity by depth and signal attenuation (dB/mm) in both cross-sectional and en-face orientation. A decision tree model was constructed to combine measured VLE parameters and delineate diagnostic thresholds. Results Thirty EMR scans were obtained – 15 T1a specimens from 9 patients and 15 T1b specimens from 11 patients. T1b specimen VLE scans exhibited higher signal intensity (P < 0.0001) and higher signal attenuation compared to T1a specimens (P = 0.03). A combination of signal attenuation and signal intensity at 150 µm depth yielded optimal diagnostic thresholds and an area under the curve (AUC) of 0.77. VLE signal attenuation was significantly associated with grade of differentiation, irrespective of EAC stage. Conclusions VLE signal intensity and signal attenuation are quantitatively distinct in T1a and T1b EAC and associated with grade of differentiation. This is the first study examining the role of VLE for staging of T1 EAC and demonstrates promising diagnostic performance. With further in vivo validation, VLE may serve a role in staging superficial EAC.